Biodegradation of aliphatic and polycyclic aromatic hydrocarbons in seawater by autochthonous microorganisms. (November 2019) - Pereira, Evandro; Napp, Amanda P.; Allebrandt, Sara; Barbosa, Renê; Reuwsaat, Júlia; Lopes, William; Kmetzsch, Lívia; Staats, Charley C.; Schrank, Augusto; Dallegrave, Alexsandro; Peralba, Maria do Carmo R.; Passaglia, Luciane M.P.; et al.
Abstract: The bioremediation of petroleum spills in marine environments is still a challenge nowadays, and the technology available towards this goal must be improved. The search for efficient and applicable systems requires the prospection, isolation and characterization of autochthonous microorganisms with potential for bioremediation. Here, microorganisms were isolated from "Lagoa do Peixe" National Park, a site with a history of frequent petroleum spills in Brazil. The isolation methodology was based on the enrichment of microorganisms able to biodegrade petroleum hydrocarbons. After preliminary tests of 2, 3, 5-triphenyl tetrazolium chloride (TTC) redox indicator, two bacteria were able to produce biosurfactants and metabolize complex carbon sources in a solid medium: Bacillus methylotrophicus SSNPLPB5 and Pseudomonas sihuiensis SNPLPB7. Biodegradation assays using aliphatic and polycyclic aromatic hydrocarbons (PAHs) sources showed that both bacteria are able to biodegrade: ( i ) up to 92.1% and 42.4% of the medium (C8 to C19) and long (C20 to C33) chain aliphatic contaminant fraction, respectively; ( ii ) 31.1% of isoprenoid (pristane) and ( iii ) 46% of anthracene, 33.9% of phenanthrene and 35.3% of pyrene, after 46 days of incubation in seawater. The isolates were shown to produce biosurfactants such as surfactins, iturins, mono- and di-rhamnolipids, which reduced the surface tension, pH and showed emulsifying activity of the cell-free supernatant at the end of the incubation time, with potential application in petroleum spills bioremediation. Highlights: Autochthonous isolates showed high ability to biodegrade Bazu petroleum in seawater. The selected bacteria showed stability under conditions of salinity, nutrition and pH of seawater. The biosurfactants: surfactins, iturins and rhamnolipids were identified. The strains are prospective for removing petroleum hydrocarbons from marine environment.